Modern Possibilities of Using Lactulose in Clinical Practice - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of  the publication. To present an overview  of current literature data on the possibilities of application  of lactulose in clinical practice.Key findings. Lactulose is a synthetic disaccharide belonging to the class of osmotic laxatives. Officially  permitted indications for its appointment in Russian Federation are functional constipation (including in children, the elderly and senile, pregnant women and women in postpartum period), an obstipation type of irritable bowel syndrome, the need to soften the consistency of feces in hemorrhoids and anal fissures, after operations on the colon and anorectal area,   as well as hepatic encephalopathy.  Other  indications include preparation for colonoscopy, treatment and prevention of disorders of the intestinal microbiota, prevention  of constipation in oncological  patients receiving narcotic analgesics, as well as patients on artificial lung ventilation.Conclusion. Lactulose is a highly effective  and safe drug, which combines osmotic laxative effect with expressed prebiotic action and is used in a wide clinical practice.